Integration of Islamic Da'wah Principles in Business Operations: A Study of Haryanto Bus Company Boyolali - Setiawan, Hafidz Dharma; Bahiroh, Siti; Tahir, Kartini Radjabulan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
This research aims to explore the process of internalizing Islamic da'wah values in the management of the Haryanto bus company, especially in the Boyolali garage. The method used is a descriptive qualitative approach with interviews, observations, and documentation as data collection techniques. The results of the study show that the process of internalizing the values of Islamic da'wah and Islamic da'wah carried out by H. Haryanto is in the form of worship activities such as congregational prayers, almsgiving, and awarding in the form of Umrah. In addition, adequate worship facilities and corporate rules that support social charity reinforce the internalization of these values. However, there are factors that hinder the process of internalizing Islamic da'wah values such as the physical limitations of leaders and working hours that clash with worship times. The impact of the application of Islamic da'wah values in the company is proven to create a harmonious and productive work environment, as well as improve employee discipline. The implication of this research is that the internalization of Islamic da'wah values in the company not only achieves worldly success but also obtains moral and spiritual blessings for every karwayan. This research contributes to understanding how faith-based leadership can be applied in organizations and opens up opportunities for further research on the long-term impact of internalizing religious values in the workplace.